Adventureman, volume 3 ebook Ghost lights. - Fraction, Matt (Adventureman, 2024)
The thrilling ADVENTUREMAN saga continues as Claire and her family find themselves drawn into an old war waged by a ghostly gangland empire, and the new realities of a life lived in the old-fashioned pulp hero world of Adventureman set in. High adventure, all-ages action, and spectacular thrills abound in a gorgeous new volume by this award-winning team. Collects ADVENTUREMAN: GHOST LIGHTS #1-2